Comparative Effectiveness of Approaches to Students’ Labour Education in Universities in the New Era With the Use of Information Technologies - Xu, Ting (International Review of Research in Open and Distributed Learning, 2025)
This study aimed to identify and compare the efficiency of different theoretical (competence-oriented) and practical (system-activity) approaches to labour education of college students in China using the Open edX online learning platform. The study was conducted at the Shengda College of Economics and Business Management. It involved 150 first-year college students and two full-time teacher-employees from the Labour Protection Department who had responsibility to ensure the quality of labour education and supervise the process of its introduction. The practical approach was 75% more effective when college students were allowed to choose work according to their preferences. The study showed that the practical approach decreased students’ motivation to work by 3%, while the average motivation with a theoretical approach was 45% higher than with a practical one, due to lack of physical work and exhaustion at work.